1998
DOI: 10.1016/s0306-4522(97)00530-7
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory control of somatodendritic interactions underlying action potentials in neocortical pyramidal neurons in vivo: An intracellular and computational study

Abstract: Abstract--The effect of synaptic inputs on somatodendritic interactions during action potentials was investigated, in the cat, using in vivo intracellular recording and computational models of neocortical pyramidal cells. An array of 10 microelectrodes, each ending at a different cortical depth, was used to preferentially evoke synaptic inputs to different somatodendritic regions. Relative to action potentials evoked by current injection, spikes elicited by cortical microstimuli were reduced in amplitude and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 75 publications
(104 reference statements)
3
42
0
1
Order By: Relevance
“…Other contributions to spike shape might come from the properties of the dendritic tree. An in vivo analysis and a detailed model have shown that dendritic sodium channels contribute to spike shape (Paré et al, 1998). Models using four compartments reproduce this result for the naturalistic stimulation used experimentally and suggest that, at least in the model, this effect is smaller than that of the conductance history (Supplement 3, available at www.jneurosci.org as supplemental material).…”
Section: Encoding Into Spike Shapes In a Model Of Cortical Neuronmentioning
confidence: 83%
See 1 more Smart Citation
“…Other contributions to spike shape might come from the properties of the dendritic tree. An in vivo analysis and a detailed model have shown that dendritic sodium channels contribute to spike shape (Paré et al, 1998). Models using four compartments reproduce this result for the naturalistic stimulation used experimentally and suggest that, at least in the model, this effect is smaller than that of the conductance history (Supplement 3, available at www.jneurosci.org as supplemental material).…”
Section: Encoding Into Spike Shapes In a Model Of Cortical Neuronmentioning
confidence: 83%
“…An influence of action potential shape was evident only from differences between pyramidal and Purkinje neurons and from modeling. A possible mechanism for variability in the action potential shape within a neuron is the variable participation of dendritic sodium currents, which can be prevented by proximal IPSPs (Paré et al, 1998). …”
Section: Introductionmentioning
confidence: 99%
“…In vivo, the depolarizing effect would be greatest during periods of slow firing and for neurons with large afterhyperpolarizations that go below E rev . If E rev were significantly more negative (e.g., approximately Ϫ75 mV), as has been suggested by some in vivo intracellular studies in adult cortex (Pare et al, 1998), the depolarizing effect would become less significant.…”
Section: Processes That Mediate the Effects Of G Inhmentioning
confidence: 85%
“…n syn represents the total number of synapses for a given cell-cell connection and is taken from data when possible (Douglas and Martin 1990;Krimer and Goldman-Rakic 2001;Kalisman et al 2003;Kisvárday et al 2002;DeFelipe 1985). R j represents a factor for the relative receptor density, is taken as 1 for excitatory cells, and derived from (Paré et al 1998) for the inhibitory cell types. Table 3 Single neuron simulations using modified Hodgkin-Huxley equations with calcium diffusion.…”
Section: A3 Synaptic Propertiesmentioning
confidence: 99%